Outbreak Bias in Illness Reporting and Case Confirmation in Ciguatera Fish Poisoning Surveillance in South Florida - Begier, Elizabeth M. (Association of Schools of Public Health, 2006)
OBJECTIVE: Ciguatera fish poisoning is a potentially life-threatening disease caused by eating coral reef fish contaminated with ciguatoxins and is the most common marine poisoning. However, existing surveillance systems capture few cases. To improve regional ciguatera surveillance in South Florida, this study compared ciguatera illnesses in the Florida Poison Information Center–Miami (FPICM) call database to ciguatera cases in the Florida Department of Health (FDOH) disease surveillance systems. METHODS: Univariate and multivariate logistic regression were used to identify predictors of when FPICM reported ciguatera illnesses to FDOH and whether FDOH confirmed reported ciguatera cases. RESULTS: FPICM staff preferentially reported ciguatera illnesses that were of shorter duration (adjusted odds ratio [AOR]=0.84 per additional illness day; 95% confidence interval [CI] 0.74, 0.97); outbreak-associated (AOR=7.0; 95% CI 2.5, 19.5); and clinically more severe (AOR=21.6; 95% CI 2.3, 198.5). Among ciguatera illnesses reported to FDOH, outbreak-associated illnesses were more likely than single, sporadic illnesses to become confirmed surveillance cases (crude OR=11.1; 95% CI 2.0, 62.5). CONCLUSIONS: The over-representation of outbreak-associated ciguatera cases underestimates the true contribution of sporadic illnesses to ciguatera disease burden. This bias should be considered when evaluating surveillance systems that include both outbreak-associated and sporadic illness reports.